(untitled) (Journal of the College of Basic Education, 2022)
After the exploratory study conducted by the researcher on a group of decorative formations employed on Islamic artifacts transferred with various materials and collectibles, in the Abbasid era (1236 AH - 850 AD / 1200 AH - 1786 AD), in the state of Iraq, it was found that there are personal, sensory and cognitive motives.The researcher raised a number of questions, including, why does the decorated artist resort to decorating any masterpiece he performs, and does it have anything to do with the religious aspects that are intended to distinguish the new religion (Islamic) from other religions (religious influence)